2021
DOI: 10.3390/ijerph182211799
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Scientific Studies and Case Reports on Music and Obsessive-Compulsive Disorder

Abstract: Obsessive-compulsive disorder (OCD) is a severe psychiatric disorder, which can be associated with music-related symptoms. Music may also be used as an adjunct treatment for OCD. Following the PRISMA guidelines, we performed a systematic literature review exploring the relationship between music and OCD by using three online databases: PubMed, the Web of Science, and PsycINFO. The search terms were “obsessive compulsive disorder”, “OCD”, “music”, and “music therapy”. A total of 27 articles were utilised (n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
(127 reference statements)
0
8
0
Order By: Relevance
“…This underscores the need for studies to improve results in this regard. Few studies have explored the impact of exposure to music on obsessive–compulsive symptoms, with limited data suggesting a positive role of music in this specific psychological disorder [ 59 ]. Our findings imply that external elements, such as music, can help patients shift their focus away from negative emotional states that could be linked to rumination and disruptive thoughts [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This underscores the need for studies to improve results in this regard. Few studies have explored the impact of exposure to music on obsessive–compulsive symptoms, with limited data suggesting a positive role of music in this specific psychological disorder [ 59 ]. Our findings imply that external elements, such as music, can help patients shift their focus away from negative emotional states that could be linked to rumination and disruptive thoughts [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have explored the impact of exposure to music on obsessive–compulsive symptoms, with limited data suggesting a positive role of music in this specific psychological disorder [ 59 ]. Our findings imply that external elements, such as music, can help patients shift their focus away from negative emotional states that could be linked to rumination and disruptive thoughts [ 59 , 60 ]. Additionally, our results support the potential of music in reducing the degradation of positive emotions, although more research is warranted to dive into this area.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent systematic review of music and OCD found three studies examining the use of music therapy as an adjunct to standard treatment for patients with OCD [ 96 ]. Two of the studies used receptive music therapy, which involved listening to classical music: one study implemented daily, 50-min sessions over a three-month period and the other used 12 sessions of listening over a span of four weeks.…”
Section: Other Therapiesmentioning
confidence: 99%
“…Both studies found significantly less severe obsessive symptoms compared to the control groups who received standard treatment only. A third study reviewed by Truong et al [ 96 ] examined improvisational music therapy and music listening sessions as adjunctive treatments for re-socializing in a sample of 24 patients but only two of them were diagnosed with OCD (with the remainder diagnosed with mood disorders and schizophrenia).…”
Section: Other Therapiesmentioning
confidence: 99%
“…Music therapy (MT) is the use of music by trained and credentialed professionals to provide benefit to an individual through enabling treatment, enhancing their recovery, or generally improving their well-being [ 19 ]. Despite being traditionally regarded as an alternative or complementary therapy, research findings that indicate the benefits of MT for different psychiatric conditions are increasingly common [ 20 ], including for psychotic illnesses [ 21 ]; autism spectrum conditions [ 22 ]; and obsessive-compulsive disorder [ 23 ]. Music is unique in its ability to generate and intensify different types of emotions [ 24 ], and it therefore offers an exciting area of potential therapeutic benefits for people with emotional difficulties.…”
Section: Introductionmentioning
confidence: 99%